Epidemiology of multidrug-resistant organisms before and during COVID-19 in Hong Kong - Shuk-Ching Wong; Pui-Hing Chau; Simon Yung-Chun So; Kelvin Hei-Yeung Chiu; Lithia Lai-Ha Yuen; Christine Ho-Yan AuYeung; Germaine Kit-Ming Lam; Veronica Wing-Man Chan; Jonathan Hon-Kwan Chen; Hong Chen; Xin Li; Pak-Leung Ho; et al. (Elsevier, 2023)
SUMMARY: Background: The coronavirus disease 2019 (COVID-19) has influenced antimicrobial consumption and incidence of multidrug-resistant organisms (MDROs). We aimed to study the epidemiology of MDROs before and during the COVID-19 pandemic in Hong Kong. Methods: With the maintenance of infection control measures, we described the trend of MDRO infections, including methicillin-resistant Staphylococcus aureus (MRSA), carbapenem-resistant Acinetobacter species (CRA), and extended-spectrum-beta-lactamase-(ESBL)-producing Enterobacterales, in a healthcare region with 3100-bed before (1 January 2016 to 31 December 2019, period 1) and during COVID-19 (1 January 2020 to 30 September 2022, period 2), together with the antimicrobial consumption using piecewise Poisson regression. The epidemiological characteristics of newly diagnosed COVID-19 patients with or without MDRO infections were analyzed. Results: Between period 1 and 2, we observed a significant increase in the trend of CRA infections (P<0.001), while there was no significant increase in the trend of MRSA (P=0.742) and ESBL-producing Enterobacterales (P=0.061) infections. Meanwhile, a significant increase in the trend of carbapenems (P<0.001), extended-spectrum beta-lactam-beta-lactamase inhibitor combinations (BLBI) (P=0.045), and fluoroquinolones (P=0.009) consumption was observed. The observed opportunity (23,540 ± 3703 vs 26,145 ± 2838, p=0.359) and compliance (81.6% ± 0.5% vs 80.1% ± 0.8%, P=0.209) of hand hygiene per year was maintained. In a multivariable model, older age, male sex, referral from residential care home for the elderly, presence of indwelling device, presence of endotracheal tube, and use of carbapenems, use of BLBI, use of proton pump inhibitors and history of hospitalization in the past 3 months were associated with higher risks of infections by MDROs among COVID-19 patients. Conclusion: Infection control measures may control the surge of MDROs despite an increasing trend of antimicrobial consumption.